2017
DOI: 10.1093/neuonc/nox159
|View full text |Cite
|
Sign up to set email alerts
|

Early posttreatment assessment of MRI perfusion biomarkers can predict long-term response of lung cancer brain metastases to stereotactic radiosurgery

Abstract: Posttreatment Ktrans SD may be used as an early posttreatment imaging biomarker to help predict long-term response of lung cancer brain metastases to SRS. This can help identify patients who will ultimately fail SRS and allow for timelier adjustment in treatment approach. These data should be prospectively validated in larger patient cohorts and other histologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…On the contrary, Winter et al [36] found significant decreases in v e at 20 days post stereotactic radiosurgery for brain metastases. Furthermore, most studies do not find a significant change in v e following therapy [34][35][36]39,41]. These variable results may be due to the long scan times required for precise measurement of v e [5,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, Winter et al [36] found significant decreases in v e at 20 days post stereotactic radiosurgery for brain metastases. Furthermore, most studies do not find a significant change in v e following therapy [34][35][36]39,41]. These variable results may be due to the long scan times required for precise measurement of v e [5,46].…”
Section: Discussionmentioning
confidence: 99%
“…A recent early stage breast cancer study [13] found significant increases in the initial area under an enhancement curve for the entire GTV at one-week post-single dose SABR. However, when assessing response at later times (>1month) in other cancer sites, decreases in K trans were associated with pathologically complete response [39][40][41]. Two of these reports [39,41] also indicated that decreases in rK trans was indicative of response.…”
Section: Discussionmentioning
confidence: 99%
“…v e and K trans are derived from DCE-MRI, which has been extensively utilized to evaluate brain tumors. 9,19,20,[30][31][32] For example, Taunk et al found that post-SRS K trans standard deviation within 12 weeks of treatment was a significant predictive biomarker for lung cancer brain metastases. Almeida-Freitas et al found that an increase of 15% in K trans 4-8 weeks after SRS was predictive of tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, early apoptotic changes may precede tumor shrinkage; these changes cannot be assessed with conventional imaging and typically require follow-up over months to years. 5 Multiple studies have assessed the predictive capabilities of conventional and advanced MRI features weeks to months after SRS [5][6][7][8][9] with mixed results using mainly retrospective analysis. Advanced MRI hours after treatment may better predict long-term treatment response.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work showed that a DCE-MRI permeability decrease within brain metastases at 1 week post-SRS was predictive of treatment response [ 7 ], although differences in permeability quantification make direct comparisons with the cited study challenging. Another study, investigating predictive value of DCE-MRI metrics < 12 weeks post-SRS, demonstrated decreased K trans and v e measures post-SRS in non-progressing metastases, although their key result was demonstrating predictive value of post-contrast K trans standard deviation for distinguishing progressing versus non-progressing metastases [ 20 ]. Both increases [ 21 ] and decreases [ 7 ] in DSC measures of rCBV have been observed in progressive disease versus non-progressive disease after 4–6 weeks post-RT.…”
Section: Discussionmentioning
confidence: 99%